Development of an international template to support patient submissions in Health Technology Assessments. (1st April 2021) - Cook, Nigel; Livingstone, Heidi; Dickson, Jennifer; Taylor, Louise; Morgan, Kate; Coombes, Martin; Wortley, Sally; Oehrlein, Elisabeth; Vicente-Edo, María José; Waibel, Franz; Liden, Barry
Abstract: Objectives: To develop an international template to support patient submissions in Health Technology Assessments (HTAs). This was to be based on the experience and feedback from the implementation and use of the Scottish Medicines Consortium's (SMC) Summary Information for Patient Groups (SIP). Methods: To gather feedback on the SMC experience, web-based surveys were conducted with pharmaceutical companies and patient groups familiar with the SMC SIP. Semistructured interviews with representatives from HTA bodies were undertaken, along with patient group discussions with those less familiar with the SIP, to explore issues around the approach. These qualitative data informed the development of an international SIP template. Results: Survey data indicated that 82 percent (18 of 22 respondents) of pharmaceutical company representatives felt that the SIP was worthwhile; 88 percent (15/17) of patient group respondents found the SIP helpful. Both groups highlighted the need for additional support and guidance around plain language summaries. Further suggestions included provision of a glossary of terms and cost-effectiveness information. Patient group interviews supported the survey findings and led to the development of a new template. HTA bodies raised potential challenges around buy-in, timing, and bias connected to the SIP approach. Conclusions: The international SIP template is another approach to support deliberative processes in HTA. Although challenges remain around writing summaries for lay audiences, along with feasibility considerations for HTA bodies, the SIP approach should support more meaningful patient involvement in HTAs.